Udział diety i aktywności fizycznej w życiu kobiet pracujących umysłowo = Influence of a diet and physical activity on the prevention of selected civilization diseases on the basis of research conducted on the group of female white collar workers - Szczepanowska, Ewa; Sarzała, Tomasz; Zamaro, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the problem of civilization diseases among female white collar workers. The aim was to prove the relationship between the applied diet and practiced physical activity, and civilization diseases.
Keywords: women; mental work; physical activity; diet; kobiety; praca umysłowa; aktywność fizyczna; dieta